1996
DOI: 10.1016/0736-5748(96)00094-9
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan restriction causes long‐term plastic changes in corticofrontal pyramidal neurons

Abstract: A Golgi study of third-layer pyramidal neurons from the corticofrontal cortex of tryptophan-restricted rats was carried out. At 40 days of age, dendritic arborization from treated rats was less profuse than that seen in control rats, and enlargement of dendritic processes, as well as an increase of the number of dendritic spines, were observed in 60-day-old rats. These plastic responses could be mediated either by a decrease in serotonin, which acts on the serotoninergic receptors of pyramidal neurons, or thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 30 publications
(4 reference statements)
1
7
0
Order By: Relevance
“…Here, we found that transient 5‐HT depletion led to a permanent reduction in dendritic complexity of pyramidal neurons in layers III and V of the somatosensory cortex. Interestingly, this effect is similar to that induced by a low‐tryptophan diet (Gonzalez‐Burgos et al ., 1996; Feria‐Velasco et al ., 2002). Indeed, diets that restrict tryptophan intake, the essential amino acid necessary for 5‐HT synthesis, have been found to reduce dendritic arborization and number of dendritic spines of pyramidal neurons in the hippocampus and in layer III of the prefrontal cortex.…”
Section: Discussionsupporting
confidence: 79%
“…Here, we found that transient 5‐HT depletion led to a permanent reduction in dendritic complexity of pyramidal neurons in layers III and V of the somatosensory cortex. Interestingly, this effect is similar to that induced by a low‐tryptophan diet (Gonzalez‐Burgos et al ., 1996; Feria‐Velasco et al ., 2002). Indeed, diets that restrict tryptophan intake, the essential amino acid necessary for 5‐HT synthesis, have been found to reduce dendritic arborization and number of dendritic spines of pyramidal neurons in the hippocampus and in layer III of the prefrontal cortex.…”
Section: Discussionsupporting
confidence: 79%
“…It is well known that axons coming from the rostral raphe nuclei provide major serotonergic projections to the forebrain and hippocampus (Azmitia and Segal, 1978;Datiche et al, 1995;Freund et al, 1990;Pérez-Vega et al, 2000). Data from our laboratory show an increment in the number of dendritic spines in the pyramidal cells of the prefontral cerebral cortex in both, the rats fed with a diet restricted in TRY (González-Burgos et al, 1996), and under conditions of selective pharmacological lesion of the dorsal raphe nucleus in rats (Pérez-Vega et al, 2000).…”
Section: Role Of 5-ht In Brain Developmentmentioning
confidence: 64%
“…Side effects to the reduction of 5-HT due to a diminishing of that indolamine producing neurons might be related to disturbances on behavioral manifestations where 5-HT is involved (González-Burgos et al, 1996). This neurotransmitter is directly related to sleep-awake cycles, depressive conditions, anxiety, feeding, pain control and sexual behaviors (Fernstrom, 1981;Tissari and Tikkanem, 1977).…”
Section: Role Of 5-ht In Brain Developmentmentioning
confidence: 99%
“…Animals fed with low tryptophan diet [197,198] display cortical pyramidal neurons with decreased dendritic complexity and spine density. Thus, 5-HT may regulate dendritic maturation and spine density through different types of 5-HT receptors that remain to be identified.…”
Section: Serotonin and Dendritic Maturation Of Cortical Neuronsmentioning
confidence: 99%